COVID 19- A new challenge for safer antenatal care (Panacea Journal of Medical Sciences, 2024)
Background: Antenatal care (ANC) is an indispensable component in the life of every expectant mother. Pregnancy per say is associated with physiological changes some of which may be undesirable like nausea, vomiting of pregnancy and may adversely affect the quality of life of the pregnant mother. The ongoing COVID pandemic continues to pose as a new challenge for safe and effective ANC due to very limited evidence available. COVID can cause severe disease in certain groups of population including mortality warranting extensive research. As of now standard protocol is lacking and social distancing appears to be the best possible preventive mechanism. This study aims to assess the benefits of protocolled Antenatal care during the COVID pandemic.Materials and Methods: Present study was done at the obstetric department of two hospitals in Mumbai. 1500 expectant mothers satisfying the necessary criteria were enrolled.Results: Most of the women in the study group were primi. They were enrolled for check-ups as per the study protocol. Normal delivery was conducted in 65 percent of cases and LSCS was performed for indicated cases only.Conclusions: Antenatal care in COVID is a new challenge we are facing globally. A systematic protocol is eminent for the ANC in pandemic which is cost effective with easy learning curve. Nevertheless social distancing, personal hygiene including hand sanitizers, appropriate PPE will offer the best preventive measure for the COVID-19.